2019
DOI: 10.3389/fevo.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Transcription at Venom Genes and Its Role as a Complementary Mechanism for the Generation of Venom Complexity in the Common House Spider

Abstract: The complex composition of venom, a proteinaceous secretion used by diverse animal groups for predation or defense, is typically viewed as being driven by gene duplication in conjunction with positive selection, leading to large families of diversified toxins with selective venom gland expression. Yet, the production of alternative transcripts at venom genes is often overlooked as another potentially important process that could contribute proteins to venom, and requires comprehensive datasets integrating geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 86 publications
(111 reference statements)
0
28
0
Order By: Relevance
“…Interestingly, a similar case has been recently described in a study comparing the transcriptomes of venom glands, silk glands, ovaries, and the prosoma without the venom glands of Parasteatoda tepidariorum ([23] STable6). The authors reported that “in contrast with the selective expression in the venom gland as posited in the traditional model of venom evolution …, many of the individual transcripts that produce venom proteins in this study have some level of expression in other tissues (silk, ovary, or cephalothorax).” [23]. The exact sequencing conditions including multiplexing level and samples multiplexed are not disclosed.…”
Section: Analysis Of Venom Componentsmentioning
confidence: 56%
See 1 more Smart Citation
“…Interestingly, a similar case has been recently described in a study comparing the transcriptomes of venom glands, silk glands, ovaries, and the prosoma without the venom glands of Parasteatoda tepidariorum ([23] STable6). The authors reported that “in contrast with the selective expression in the venom gland as posited in the traditional model of venom evolution …, many of the individual transcripts that produce venom proteins in this study have some level of expression in other tissues (silk, ovary, or cephalothorax).” [23]. The exact sequencing conditions including multiplexing level and samples multiplexed are not disclosed.…”
Section: Analysis Of Venom Componentsmentioning
confidence: 56%
“…After a long period dominated by Edman degradation, new DNA sequencing techniques and soft ionization techniques for mass spectrometry (matrix-assisted laser desorption/ionization (MALDI), and electrospray ionization (ESI)) accelerated also spider venom research. Meanwhile, dozens of venom gland cDNA libraries, sequenced by Sanger, Roche 454 and Illumina techniques [16,17,18,19,20,21,22,23,24] diversified our knowledge on spider venom within less than two decades considerably. Here we review the state of the art of the composition of spider venoms and the currently available methods to analyze it.…”
Section: Introductionmentioning
confidence: 99%
“…Daboia russelii russelii (DRR) snake venom, which is known for its relatively high content of svPLA 2 , was used as a test venom for assay optimization at a concentration of 12.5 µg/mL. [11] Figure 1 shows time-course absorbance measurements in a cuvette using optimized assay conditions and DRR venom.…”
Section: Assay Optimizationmentioning
confidence: 99%
“…Venom composition is typically complex (50-200 proteins per species) and highly variable, with often extensive inter-specific, and even, intra-specific venom variations observed. [11,12] Rooted in the latter are geographical differences, living habitat, sex, and age of a snake, thereby increasing venom complexity even more. [13,14] Consequently, antivenom therapies, which are based on antibodies produced in horses or sheep following their immunization with venom or mixtures of venoms, are highly specific to those venoms used for production, but often lack efficacy for treating snakebites by other snake species.…”
Section: Introductionmentioning
confidence: 99%
“…These venoms comprise many different pathological proteins and peptides, and other organic molecules. Venom composition is typically complex (50-200 proteins per species) and highly variable, with often extensive interspecific, and even, intra-specific venom variations observed (Casewell et al, 2014;Haney et al, 2019). Rooted in the latter are geographical differences, living habitat, sex, and age of a snake, thereby increasing venom complexity even more (Calvete, 2019;Gopalakrishnakone and Calvete, 2016).…”
Section: Introductionmentioning
confidence: 99%